2022
DOI: 10.7759/cureus.30926
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Repair Modality of Perforated Peptic Ulcer: Less Is More?

Abstract: Perforation, per se, presents the most serious complication of peptic ulcer disease with a mortality rate that cannot be underestimated. Surgery is the only treatment option, which can be performed laparoscopically or via conventional laparotomy. The present study aimed to compare the short-term outcomes of laparoscopy and laparotomy techniques in the surgical treatment of peptic ulcer perforation. A retrospective study design was structured to compare the perioperative and short-term postoperative outcomes of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 30 publications
(32 reference statements)
0
5
0
3
Order By: Relevance
“…In the present study, we investigated the effect of an intraoperative warming heating blanket with forced air warming on postoperative pain and analgesic consumption in short and long laparoscopic surgical procedures. In the United Kingdom, the National Institute for Health and Care Excellence recommends the following: (i) monitoring patients' intraoperative temperature every 30 minutes; (ii) delaying anesthesia induction until the patient's body temperature rises above 36°C; (iii) warming intravenous fluids and blood products to 37°C; (iv) using a forced-air warming device placed over patients for heating purposes for procedures lasting longer than 30 minutes; and (v) if normothermia can be maintained through warmed irrigation or external warming devices, it can be concluded that there is no need for warmed insufflation systems and the additional costs they bring [ 3 , 4 , 7 ]. Herein, we planned this work with the hypothesis that hypothermia could be prevented through a patient warming procedure rather than warming and humidifying CO2 gas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, we investigated the effect of an intraoperative warming heating blanket with forced air warming on postoperative pain and analgesic consumption in short and long laparoscopic surgical procedures. In the United Kingdom, the National Institute for Health and Care Excellence recommends the following: (i) monitoring patients' intraoperative temperature every 30 minutes; (ii) delaying anesthesia induction until the patient's body temperature rises above 36°C; (iii) warming intravenous fluids and blood products to 37°C; (iv) using a forced-air warming device placed over patients for heating purposes for procedures lasting longer than 30 minutes; and (v) if normothermia can be maintained through warmed irrigation or external warming devices, it can be concluded that there is no need for warmed insufflation systems and the additional costs they bring [ 3 , 4 , 7 ]. Herein, we planned this work with the hypothesis that hypothermia could be prevented through a patient warming procedure rather than warming and humidifying CO2 gas.…”
Section: Discussionmentioning
confidence: 99%
“…Briefly, heat loss depends on the wound site, which can be more significant compared to laparoscopy in conventional surgical procedures. However, alterations in temperature due to carbon dioxide (CO2) insufflation during laparoscopic surgeries appear [2][3][4][5][6]. In addition, warming and humidification of insufflated CO2 gas have been reported in order to reduce the development of hypothermia [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Como explanado anteriormente, a cirurgia laparoscópica vem sendo correlacionada a diminuição de ocorrência de intercorrências, como pneumonia e eventos cardíacos isquêmicos Outras complicações presentes no grupo de laparotomia são deiscência da ferida (VAKAYIL et al, 2019), mais internações em terapia intensiva, mais número de lesões renais agudas e maior síndrome do desconforto respiratório agudo (JAMAL et al, 2019), taxas altas de ventilação/reintubação prolongada (DAVENPORT et al, 2018), infecção torácica (SENGUPTA et al, 2020), maior risco de sangramento (14,6% versus 8%) e pneumonia (8,7% versus 4,5%) (JAYARAMAN et al, 2021). Acerca de operações laparoscópicas minimamente invasivas, em comparação com laparotomia possuem menor ocorrência de complicações, porém a falha na sutura acontece de forma similar (PANIN et al, 2021) ou até mesmo com maior frequência, pela deiscência da sutura (TULINSKÝ et al, 2022). Há explanações quanto a ocorrência de pneumotórax pela técnica laparoscópica de omentopexia com oito suturas (YOON et al, 2019).…”
Section: Complicações Trans E Pós-operatóriasunclassified
“…Também há relatos de um tempo semelhante entre a laparoscopia e laparotomia propriamente ditas (TULINSKÝ et al, 2022;AKIN et al, 2022).Outro fator importante está relacionado aos ambientes de saúdes com recursos limitados, o tempo de internação continua favorável para técnicas laparoscópicas, com média até menores do que os encontrados em outros centros, sendo de 5,10 ± 0,87 dias (AYYAZ et al, 2022).…”
Section: Tempo De Internaçãounclassified
See 1 more Smart Citation